MAUSHUL MUSYTARAK DALAM SURAH ALI IMRAN - Fitri Ananda; Zainul Arifin; Rahmat Satria Dinata (Journal Cerdas Mahasiswa, 2022)
The holy Qur'an and its meanings have uslubs that contain miracles and beautiful wording beyond the Arabic uslubs used today. To understand the holy Qur'an, it requires the mastery of Arabic sciences, especially Nahwu science, including Ism Maushul Musytarak. Therefore, the author is interested to make a research  regarding to the nahwu science, especially in the title of "Ism Maushul Musytarok in Surah Ali-imron." The research method used is an explanatory research method with a qualitative desk research approach.Explanatory research method is a research in which the data is analyzed to determine the relationship between one variable and another. The qualitative approach is used to express the data verbally and analyze the data without statistical methods. Data collection tools include observation and documentation. After the author carried out research in surah Ali-imron so that she found 166 Ism Maushul Musytarok, namely: Al, Ma, Man, and ayyu.